Myopathy in hypophosphataemic osteomalacia presenting in adult life. Issue 3 (March 1975) - Schott, G D; Wills, M R
Abstract : Three cases of hypophosphataemic osteomalacia presenting in adult life, in which a myopathy was a prominent presenting feature, are described. In one, a nasopharyngeal haemangioma was also present. Possible mechanisms underlying the myopathy are discussed briefly.